LANGUAGE GAMES IN TEACHING AND LEARNING ENGLISH GRAMMAR - Diana Komilovna Ruzmetova (European Science Publishing, 2024)
Chalk-and-talk instruction, a traditional method of teaching and learning, is becoming obsolete in classrooms. Different task-based processes are introduced to teachers and students in order to improve student participation throughout the course. Using language games to help teach different skills is one of the most popular and favored teaching methods. Language games are now being used in classes on a more sophisticated and modern platform thanks to the rise of digital learning tools and web applications. When conducting language games during classes, teachers can better meet the needs and interests of their students by using engaging and appropriate resources and a variety of instructional strategies, particularly when it comes to teaching grammar in context. Many studies, concentrating on specific targeted language areas and skills like grammar, have used a variety of language games to demonstrate its effects on learners' knowledge, competency, and motivation in learning a language. Thus, this study will examine the use of language games in teaching and learning grammar with regard to second language (ESL) learners, based on evaluations of previous literature.
Keywords: English grammar, tools and web applications, TBLT, students’ motivation.